Automotive Ethernet switch scan wrapper chain design - Park, Chan Hyeon (Nanyang Technological University, 2023)
Since the automotive industry is facing unprecedented changes due to electric vehicles and autonomous driving cars, there is strong thirst for automotive semiconductors with extremely high reliability for utmost safety. Specifically, automotive ethernet switch, which works as a centralised communication handler between numerous sensors and the central processing unit, is one of the most promising essentials for the automotive system-on-chips. In this paper, a design-for-test issue is highlighted: dedicated wrapper cells for hierarchical design blocks the transition delay test on interface interconnections. Optimisation on the number of dedicated wrapper cells and its ratio was adopted to minimise the uncovered interconnections from the transition delay test on Marvell’s automotive ethernet switch design. Furthermore, test-related performance changes were traced with inverted hold feedback loop on wrapper cells for easier timing closure purpose. As a result, the optimised design showed a huge decrease in uncovered paths due to dedicated wrapper cells during transition delay test, while the test-related performances were improved. In addition, the performance variations trend brought by inverted hold feedback structure was studied. These results not only can give improved performances to designers who produce chips that require high reliability, but also can provide broader options on wrapper cell structures.